2018
DOI: 10.2196/jmir.9607
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Landscape of the Tertiary Referral Hospitals in China: Observational Descriptive Study

Abstract: BackgroundSocial media has penetrated all walks of life. Chinese health care institutions are increasingly utilizing social media to connect with their patients for better health service delivery. Current research has focused heavily on the use of social media in developed countries, with few studies exploring its usage in the context of developing countries, such as China. Tertiary hospitals in China are usually located in city centers, and they serve as medical hubs for multiple regions, with comprehensive a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 23 publications
0
55
0
2
Order By: Relevance
“…Larger HOs have more resources and, therefore, are more likely to implement social networks in their communication strategy [46]. According to the results presented, those HOs reach higher levels of engagement.…”
Section: Determinants Of the Level Of Users' Engagement Via Facebookmentioning
confidence: 78%
See 1 more Smart Citation
“…Larger HOs have more resources and, therefore, are more likely to implement social networks in their communication strategy [46]. According to the results presented, those HOs reach higher levels of engagement.…”
Section: Determinants Of the Level Of Users' Engagement Via Facebookmentioning
confidence: 78%
“…Nevertheless, while the only cost in the use of social media is the time involved (in contrast with traditional marketing and communication methods, which also involve costly printing and mailing), larger HOs are more likely to implement official social media accounts [46].…”
Section: Size Of the Organizationmentioning
confidence: 99%
“…It has been reported that factors including economic level, medical condition, air pollutant and environmental toxin exposure can affect the prevalence and incidence of ALS 8 20 21. East China generally has higher economic level, more tertiary hospitals and more industry associated with higher environmental pollution than other regions 36. However, reasons for the geographical variation are difficult to determine from the claims data.…”
Section: Discussionmentioning
confidence: 99%
“…In the healthcare sector, the adoption of social media is not new [10,11]. Social media has been widely adopted by patients, care-givers, and healthcare professionals, with numerous studies reporting its usefulness in patient empowerment, health promotion, patient-physician relationship building, public health surveillance, and quality improvement [12][13][14][15][16][17]. On the contrary, other studies have focused on revealing the dark side of social media in healthcare; for example, examining how unverified content leads to the sharing of misleading information [18], patients becoming overconfident in their own medical decision making [19,20], and privacy violation [18,21].…”
Section: Social Media Use By Healthcare Departmentsmentioning
confidence: 99%